How to lose a war the story of America's intervention in Afghanistan - Saikal, Amin 1950- (Yale University Press, 2024)
"In 1958, Richard Nixon described Afghanistan as "unconquerable." On 15 August 2021, he was proven right. After twenty years of intervention, US and NATO forces retreated, enabling the Taliban to return to power. Tens of thousands were killed in the long, unwinnable war, and millions more were displaced - leaving the future of Afghanistan hanging in the balance. Leading expert Amin Saikal traces the full story of America's intervention, from 9/11 to the present crisis. After an initial swift military strike, the US became embroiled in a drawn-out struggle to change Afghanistan but failed to achieve its aims. Saikal shows how this failure was underlined by protracted attempts to capture Osama bin Laden, an inability to secure a viable government via "democracy promotion" efforts, and lack of wider strategy in the "war on terror." How to Lose a War offers an insightful account of one of the US's most significant foreign policy failures - and considers its dire consequences for the people of Afghanistan."
Literaturverzeichnis: Seite 267-293, Register
Keywords: Geschichte; Afghanistankrieg -- 2001-2021